2014
DOI: 10.1126/science.1242281
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity of epithelial stem cells in tissue regeneration

Abstract: Tissues rely upon stem cells for homeostasis and repair. Recent studies show that the fate and multilineage potential of epithelial stem cells can change depending on whether a stem cell exists within its resident niche and responds to normal tissue homeostasis, whether it is mobilized to repair a wound, or whether it is taken from its niche and challenged to de novo tissue morphogenesis after transplantation. In this Review, we discuss how different populations of naturally lineage-restricted stem cells and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
432
0
8

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 508 publications
(458 citation statements)
references
References 100 publications
10
432
0
8
Order By: Relevance
“…34 In spite of these and other findings, however, it has recently been proposed that IFE-derived cells, but not HF-derived cells, are the major long-term contributors to wound healing. 18 While previous studies have focused on whether keratinocyte stem cell sub-populations differ in their innate ability to persist in the wound, the potential influence of extrinsic, non-genetic factors affecting wound healing contributions have been largely overlooked. In this study, we speculate that the population shifts observed during regeneration can be largely explained by several such factors, including basal versus suprabasal cell position, spatial constraint and distance from the wound.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…34 In spite of these and other findings, however, it has recently been proposed that IFE-derived cells, but not HF-derived cells, are the major long-term contributors to wound healing. 18 While previous studies have focused on whether keratinocyte stem cell sub-populations differ in their innate ability to persist in the wound, the potential influence of extrinsic, non-genetic factors affecting wound healing contributions have been largely overlooked. In this study, we speculate that the population shifts observed during regeneration can be largely explained by several such factors, including basal versus suprabasal cell position, spatial constraint and distance from the wound.…”
Section: Discussionmentioning
confidence: 99%
“…17 While it is clear that multiple epithelial stem cell sub-populations can enter the wound, a more general question remains: What is the overall HF and IFE contribution to wound healing over time? Although recent reports have suggested that most HFderived cells are eventually lost and replaced by IFE-derived cells, 18 we initiated this study to better understand the kinetics underlying these population shifts. To do so, we have performed genetic fate mapping studies to document the dynamic rise and fall of HF-and IFE-derived cells in the wound over time.…”
Section: Introductionmentioning
confidence: 99%
“…radiation). The current state of the field has been recently reviewed in detail (46). The authors note that numerous lineage-tracing experiments indicate that CBC cells behave as interconvertible multipotent intestinal stem cells (2,(47)(48)(49)(50).…”
Section: Characterization Of Crypt-based Stem Cell Subtypesmentioning
confidence: 99%
“…Aging not only affects stem cells in their potential for self-renewal and differentiation, it also impacts wound closure. Said effects are primarily attributed to mitochondrial dysfunction and increased oxidative stress [ 39 ] , epigenetic regulation [ 42 ] , or disturbances in the resident niche [ 43 ] . Sequelae may include local depletion of epidermal cells and escape from the quiescence phase, and thus explain the observation that epidermal skin cells at the wound margins of chronic venous ulcers are hyperproliferative, nonmigratory, and healing-incompetent [ 44 ] .…”
Section: Stem Cell Dysfunction In Chronic Woundsmentioning
confidence: 99%